A MORPHOPHONOLOGICAL ANALYSIS OF -UM- IN JAVANESE - NFN Ekarina (Linguistik Indonesia, 2023)
This paper investigates the derivation of words through the process of Infixation. Specifically, Prince & McCarthy’s morphologically-driven Phonological Readjustment theory and Yu’s phonologically-driven Phonological Subcategorizationtheory are compared to determine which of the two is better fit to explain -um- Infixation in Javanese. I show here that Javanese infixation data is crucial in providing insight into this debate, because unlike other previously studied infixation cases, the Javanese -um- always triggers some phonological readjustment(s). This provides overwhelming evidence for the morphologically-driven Phonological Readjustment theory, as this theory is the one that can offer (i) a unified target for infixation in Javanese, and (ii) a phonologically-driven motivation for the derived words.